Managing Leaks and Fistulas After Laparoscopic Sleeve Gastrectomy: Challenges and Solutions - Gipe J; Agathis AZ; Nguyen SQ (Clinical and Experimental Gastroenterology)
Jordan Gipe, Alexandra Z Agathis, SQ Nguyen Department of Surgery, Mount Sinai Hospital, New York, NY, USACorrespondence: Jordan Gipe, Department of Surgery Box 1259 The Mount Sinai Hospital, 1 Gustave L. Levy Place, New York, NY, 10029, Tel +1818-935-3352, Email Jordan.Gipe@mountsinai.orgAbstract: Postoperative leaks after sleeve gastrectomy are a troublesome complication that occur in 0.7– 5.3% of cases depending on the referenced source. These complications cause significant morbidity for patients requiring prolonged hospitalizations, nutritional support, intravenous antibiotics, and at times additional operations and procedures that risk further downstream complications. The patient presentation varies from relatively benign with minimal or no symptomatology, to the acutely ill with life-threatening sepsis. The management of gastric leak is dependent on a multitude of factors, including the initial presentation as well the surgeon’s experience and preference. Here, we will summarize the current literature and discuss the different options that exist for the management of gastric leaks after sleeve gastrectomy including laparoscopic lavage, endoscopic stenting, endoscopic pigtail catheters, endoscopic vacuum therapy, and salvage surgical operations such as fistula jejunostomy and total gastrectomy. The aim is to provide a source for surgeons to reference when they encounter this disease pathology and to shed light on a daunting challenge for the modern bariatric surgeon.Keywords: sleeve gastrectomy, leak, fistula, management